Comprehensive Study of Li Deposition and Solid Electrolyte Cracking by Integrating Simulation and Experimental Data - Chen Lin; Haihui Ruan; Ming‐Sheng Wang (Advanced Science)
Abstract Lithium (Li) penetration into solid‐state electrolytes (SE) is a major cause of lithium‐metal solid‐state battery (LMSSB) failure. However, no single model fully explains experimental phenomena, and many simulation‐based conclusions lack validation or contradict experimental results, hindering the understanding of failure mechanisms. This study integrates simulation and experimental data to investigate Li deposition and SE cracking, introducing a unified phase‐field (PF) model. Unlike existing models, it accounts for mechanical constraints, solid–solid contact, and large‐strain mechano‐chemical coupling. It also distinguishes Li penetration from SE cracking, as short‐circuiting and cracking do not occur simultaneously. Additionally, crack initiation follows the pressurized cracking model, while propagation occurs through a wedge‐shaped opening. A counterintuitive approach to extending LMSSB lifespan is to reduce the mechanical constraints of SE rather than decreasing defect size or increasing SE hardness and toughness, provided that good contact is maintained between the electrode and SE. This is because minimizing mechanical constraints alters the Li deposition mode, preventing rapid Li eruption in cracks.